A green crack-resistant and carbon-reducing plain concrete and preparation method thereof

By using supersulfate cement and other specific ingredients, green crack-resistant carbon-reducing clean water concrete prepared, and applying nanotitanium dioxide-silane surface protectors to the surface, the problem of clean water concrete being susceptible to erosion in the natural environment is solved, achieving high strength , comprehensive effects of cracking, frost resistance and carbon reduction.

CN117342851BActive Publication Date: 2025-02-18CSCEC WESTERN CONSTR XINJIANG CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311272596.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-02-18
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

Existing clean water concrete is susceptible to erosion in the natural environment, resulting in surface microcracks, cracks, fall off and steel bar corrosion, affecting the aesthetics and stability of the building. It is difficult for the existing technology to effectively solve problems such as crack resistance and frost resistance.

Method used

Using ultrasulfate cement as the main raw material, combined with fly ash, microsilicon powder, floating beads, expanded perlite, steel slag sand, pebbles and anti-cracking and water reducing agent, a green anti-cracking and carbon-reducing concrete is prepared. And apply nanotitanium dioxide-silane surface protector to the surface.

Benefits of technology

It significantly improves the strength, crack resistance and apparent carbon adsorption properties of clean water concrete, and has good crack resistance, freezing resistance, seepage resistance and carbon reduction characteristics, improving the durability and environmental economic benefits of the building.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a kind of crack-resistant green carbon-reducing clear water concrete, each component and its weight proportion include: 400-500 parts of super sulfate cement, 100-150 parts of fly ash, 20-30 parts of microsilica powder, 50-100 parts of floating beads, 50-90 parts of expanded perlite, 500-650 parts of steel slag sand, 900-1100 parts of pebbles, 5-15 parts of viscosity-reducing anti-cracking water reducer, 150-180 parts of water, and nano titanium dioxide-silane surface protective agent is applied to its surface at the same time; wherein, the super sulfate cement is obtained by ball milling with carbide slag cement clinker, slag and desulfurized gypsum as main raw materials. The present invention can effectively improve the strength, crack resistance and apparent carbon adsorption performance of clear water concrete, and take into account the excellent characteristics such as good crack resistance, frost resistance and impermeability resistance, high late compressive strength and carbon reduction, with good environmental and economic benefits, suitable for promotion and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a green, crack-resistant, carbon-reducing plain concrete and a preparation method thereof. Background Art

[0002] In recent years, fair-faced concrete has been increasingly used in industrial and civil construction projects. It uses the natural texture of the concrete itself and the natural state formed by the combination of bolt holes, open joints and Zen joints as decoration. It has the following advantages: 1) Save the total factory cost. Fair-faced concrete does not require any decoration on the surface. Fair-faced concrete is cast in one step, which can save the cost of plastering and surface layer, and reduce project costs; 2) Reduce maintenance costs during the construction process. Fair-faced concrete does not require plastering, which avoids quality defects such as hollowing, cracks, and falling off in general concrete structure projects, and reduces the workload, difficulty and cost of maintenance; 3) It can greatly reduce the generation of construction waste.

[0003] However, exposed to the natural environment for a long time, bare concrete is very susceptible to various erosions, which will cause microcracks on the surface, and further lead to concrete cracking, falling off, steel corrosion and other problems, thus affecting the aesthetics of the building surface and even the stability of the entire building. Existing research technologies mainly improve the fluidity and air tightness of bare concrete, and harmful substances will remain on the surface, and it is easy to have problems such as bleeding, segregation, and poor demolding. In addition, it usually does not involve the solution of anti-freeze, anti-cracking and other problems.

[0004] Therefore, further exploration of fair-faced concrete that can combine good mechanical properties, workability, crack resistance, frost resistance and other properties has important research and application significance. Summary of the invention

[0005] The purpose of the present invention is to provide a crack-resistant green carbon-reducing plain concrete, which can effectively improve the strength, crack resistance and apparent carbon adsorption performance of plain concrete, and take into account good crack resistance, frost resistance, anti-seepage performance, high later compressive strength and carbon reduction and other excellent properties, has good environmental and economic benefits, and is suitable for promotion and application.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A green anti-cracking and carbon-reducing plain concrete, wherein the components and their weight proportions include: 400-500 parts of super-sulfated cement, 100-150 parts of fly ash, 20-30 parts of microsilica powder, 50-100 parts of floating beads, 50-90 parts of expanded perlite, 500-650 parts of steel slag sand, 900-1100 parts of pebbles, 5-15 parts of viscosity-reducing anti-cracking water-reducing agent, 150-180 parts of water, and a nano-titanium dioxide-silane surface protective agent is applied on the surface of the concrete; wherein the super-sulfated cement is obtained by ball milling carbide slag cement clinker, slag and desulfurized gypsum as main raw materials.

[0008] In the above scheme, the specific surface area of ​​the supersulfate cement is 380~420m 2 / kg, and the 28d strength is 45.6~49.5MPa.

[0009] In the above scheme, the raw materials in the supersulfate cement and their weight proportions include: 5-10 parts of carbide slag cement clinker, 75-85 parts of slag, and 3-8 parts of desulfurized gypsum.

[0010] In the above scheme, the content of calcium silicate mineral in the carbide slag cement clinker is 67~69wt%, the content of free calcium oxide is 1.0~1.2wt%, and the content of magnesium oxide is 0.5~0.65wt%; the content of magnesium oxide in the slag is 3.5~4.2wt%, and the sum of the contents of vitreous body and dicalcium silicate is 93~95wt%.

[0011] Furthermore, during the ball milling process, a grinding aid (preferably triethanolamine, etc.) accounting for 0.01-0.05% of the total mass of carbide slag cement clinker, slag, and desulfurized gypsum is introduced.

[0012] In the above scheme, the specific preparation method of the supersulfate cement includes: ball-milling the carbide slag cement clinker for 15 to 20 minutes while adding a grinding aid, and then adding slag and desulfurized gypsum and mixing and ball-milling for 20 to 30 minutes.

[0013] In the above scheme, the preparation method of the viscosity-reducing anti-cracking water-reducing agent comprises the following steps:

[0014] 1) Add β-naphthalenesulfonate formaldehyde condensate and polyethylene glycol laurate into water and mix evenly (20-30 minutes) to obtain a mixed solution A; dilute sodium methoxide, complex alcohol solvent and polysorbate with water and mix with the mixed solution A, and heat and stir; cool down (25-35°C); then add muscovite powder and vermiculite powder, stir twice, add tripessaponin and stir three times to obtain a mixed solution B and take it out;

[0015] 2) Under heating conditions, dodecylbenzene sulfonic acid and polyoxypropylene glycerol ether polyether modified silicone oil are added to water, stirred for four times, an initiator (such as ammonium persulfate, etc.) is added and stirred, lignin and carbon fiber are added, stirred for five times, and allowed to stand to reduce the internal temperature to 45-55°C; then mixed solution B is added, stirred for six times, and allowed to stand to reduce to room temperature (20±3°C), thereby obtaining the viscosity-reducing anti-cracking water-reducing agent.

[0016] In the above scheme, in the preparation process of the viscosity-reducing anti-cracking water-reducing agent, the raw materials and their weight proportions include: 35-55 parts of β-naphthalenesulfonate formaldehyde condensate, 25-35 parts of polyethylene glycol laurate, 2-5 parts of sodium methoxide, 6-10 parts of complex alcohol solvent (3-5 parts of ethylene glycol, 3-5 parts of methanol), 11-15 parts of polysorbate, 20-35 parts of muscovite powder, 10-25 parts of vermiculite powder, 15-35 parts of notoginseng saponin, 25-55 parts of dodecylbenzene sulfonic acid, 15-25 parts of polyoxypropylene glycerol ether polyether modified silicone oil, 10-20 parts of lignin, 5-10 parts of carbon fiber filaments, and 15-25 parts of initiator.

[0017] In the above scheme, the heating and stirring treatment step in step 1) includes: first stirring at 25-35°C for 25-30 minutes, then heating to 55-65°C and stirring for 25-30 minutes.

[0018] In the above scheme, the temperature of the second stirring treatment is 25-35°C and the time is 10-15 min; the temperature of the third stirring treatment is 25-35°C and the time is 25-30 min.

[0019] In the above scheme, the temperature of the four stirring treatments is 55-65°C and the time is 10-15 minutes; the stirring reaction time is 10-15 minutes; the temperature of the five stirring treatments is 55-65 and the time is 20-30 minutes; the six stirring treatments are 65-75 minutes.

[0020] In the above scheme, the effective solid content of the viscosity-reducing anti-cracking water-reducing agent is 20-28%.

[0021] In the above scheme, the nano titanium dioxide-silane surface protective agent has silane emulsion, nano titanium dioxide and epoxy resin as main components, silane emulsion as matrix, tetrabutyl titanate as titanium source, alcohol solvent, nitric acid and epoxy resin as composite solvent, and is prepared by sol-gel method, which specifically includes the following steps: adding the titanium source to 5-15% of the alcohol solvent, mixing evenly to obtain liquid A; adding epoxy resin and nitric acid to the remaining alcohol solvent and mixing evenly to obtain liquid B; adding liquid B dropwise to liquid A, stirring once, stopping stirring when the sol becomes milky white, and then adding the obtained titanium dioxide sol to the ultrasonically dispersed silane emulsion, stirring twice, and obtaining the nano titanium dioxide-silane surface protective agent.

[0022] In the above scheme, the raw materials in the nano titanium dioxide-silane surface protective agent and their weight proportions include: 5-15 parts of titanium source, 20-45 parts of alcohol solvent, 5-15 parts of nitric acid, 15-30 parts of epoxy resin, and 150-180 parts of silane emulsion.

[0023] In the above scheme, the titanium source can be tetrabutyl titanate or the like.

[0024] In the above scheme, the concentration of the nitric acid is 45-55wt%.

[0025] In the above scheme, the silane emulsion is isooctyl triethoxy silane emulsion with a density of 0.88-0.90 g / cm 3 , the purity is 88~92%.

[0026] In the above scheme, the dropping speed is 1-2 drops / s.

[0027] In the above scheme, the first stirring time is 25 to 45 minutes, and the second stirring time is 40 to 80 minutes.

[0028] The above-mentioned method for preparing the crack-resistant green carbon-reducing plain concrete comprises the following steps:

[0029] 1) Weigh the raw materials according to the proportion. The components and their weight proportions include: 400-500 parts of super sulfate cement, 100-150 parts of fly ash, 20-30 parts of microsilica fume, 50-100 parts of floating beads, 50-90 parts of expanded perlite, 500-650 parts of steel slag sand, 900-1100 parts of pebbles, 5-15 parts of viscosity-reducing anti-cracking water-reducing agent, and 150-180 parts of water;

[0030] 2) Use a forced mixer to mix the floating beads, expanded perlite, steel slag sand, pebbles and 30-40% of water for a first time, then add super sulfate cement, fly ash and microsilica powder for a second time, and finally add the remaining water and the viscosity-reducing anti-cracking water-reducing agent for a third time to obtain a mixture;

[0031] 3) pouring and molding the obtained mixture, applying a nano-titanium dioxide-silane surface protective agent on the surface of the obtained molded test block, and finally performing surface coating and curing to obtain the green crack-resistant and carbon-reducing plain concrete.

[0032] In the above scheme, the first mixing time is 30~45s, the second mixing time is 30~45s, and the third mixing time is 60~120s.

[0033] In the above scheme, the temperature adopted in the mixing step is room temperature, 15-25°C, and the relative humidity is above 50%.

[0034] Furthermore, the titanium dioxide-silane surface protective agent is provided by directly coating the surface of the molding test block or brushing it on the surface of the casting mold.

[0035] In the above scheme, the amount of titanium dioxide-silane surface protective agent set on the surface of the crack-resistant green carbon-reducing plain concrete is 300-500g / m 2 .

[0036] The crack-resistant green carbon-reducing plain concrete prepared according to the above scheme has a 28d compressive strength of 38~55MPa, a slump of 210~225mm, an expansion of 580~615mm, a frost resistance grade of F200~F250, a permeability grade of P20~P26, and a 3d shrinkage rate of 110×10 -6 ~250×10 -6 The total cracking area per unit area can reach 90~300mm 2 / m 2 .

[0037] The principle of the present invention is:

[0038] The present invention aims at the problems of anti-seepage, anti-cracking and anti-freezing of the whole cycle of plain concrete. Firstly, carbide slag clinker and slag are used to

[0039] As the main raw materials for preparing super sulfate cement, the lower hydration heat can make the concrete strength develop steadily and the stability is more stable.

[0040] It is determined that the secondary slag hydration of supersulfated cement makes the concrete more compact and improves the overall strength and durability of the concrete;

[0041] Secondly, in the initial stage of concrete, β-naphthalenesulfonate formaldehyde condensate, polyethylene glycol laurate, polysorbate

[0042] Anti-cracking water reducing agent supplemented by ester, muscovite powder, carbon fiber filament, etc., effectively prevents early shrinkage of concrete and enhances the quality of concrete.

[0043] machine stability, increase the density of concrete, ensure the early stability and later durability of concrete; finally, on the concrete surface

[0044] Applying titanium dioxide-silane surface protective agent can further increase the long-term weather resistance of the obtained plain concrete.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] 1) The viscosity-reducing anti-cracking water reducer of the present invention can effectively reduce the adsorption of cement soil to the water reducer, so that the materials of the plain concrete are more evenly dispersed, and the preparation method involved is relatively simple, does not require high-temperature synthesis, and has good adaptability to various environments;

[0047] 2) The carbide slag clinker used in super-sulfated cement is helpful for reducing carbon emissions in cement plants, and has lower free calcium oxide and magnesium oxide than ordinary clinker, and has better stability; the resulting super-sulfated cement is conducive to significantly reducing carbon emissions, and the preparation method involved is simple and can be used for large-scale production in cement plants;

[0048] 3) Nano-scale surface protective agent is prepared using nano-scale titanium source, which has excellent compatibility with silane emulsion, fully exerts the role of nano-titanium dioxide, is more conducive to adsorption on the concrete surface, and protects the appearance of plain concrete; it has an adsorption effect on harmful ions and carbon dioxide in the environment, which is beneficial to improving the carbon reduction level of the concrete industry. DETAILED DESCRIPTION

[0049] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. These descriptions are only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention.

[0050] The preparation steps of the viscosity-reducing anti-cracking water-reducing agent adopted are as follows: 50 parts of β-naphthalenesulfonate formaldehyde condensate and 30 parts of polyethylene glycol laurate are added to 120 parts of water and mixed for 25 minutes to obtain a mixed solution A; 3 parts of sodium methoxide, 3 parts of ethylene glycol, 3 parts of methanol and 13 parts of polysorbate (molecular weight 604) are mixed with the mixed solution A, the temperature is raised to 60°C, and stirred for 30 minutes; the temperature is lowered to 30°C; then 30 parts of muscovite powder and 15 parts of vermiculite powder are added, stirred for 15 minutes, 21 parts of Panax notoginseng saponin are added, and stirred for 28 minutes to obtain a mixed solution B and take it out; 115 parts of water are added The temperature was raised to 60°C, 35 parts of dodecylbenzene sulfonic acid and 22 parts of polyoxypropylene glycerol ether polyether modified silicone oil were added to the water, stirred for 15 minutes, 19.8 parts of initiator ammonium persulfate were added and stirred for 10 minutes, 15 parts of lignin and 7 parts of carbon fiber waste were added, stirred for 25 minutes, and allowed to stand to reduce the internal temperature to 50°C; then mixed solution B was added, stirred for 60 minutes, and allowed to stand to reduce to room temperature 22°C, to obtain the viscosity-reducing anti-cracking water-reducing agent used in the embodiment; the polyoxypropylene glycerol ether polyether modified silicone oil used was provided by Nanjing Sanshu Biology, and its density was 1.05 g / mL.

[0051] The preparation steps of the surface protective agent are as follows: add 15 parts of tetrabutyl titanate to 25 parts of isopropanol solvent, mix well, and obtain liquid A; add 25 parts of epoxy resin and 12 parts of nitric acid (concentration of 48wt%) to 16 parts of isopropanol solvent and mix well to obtain liquid B; add liquid B to liquid A at a speed of 1-2 drops / s, stir for 35 minutes, stop stirring when the sol turns milky white, and then add the obtained AB mixed solution to 165 parts of ultrasonically dispersed silane emulsion, ultrasonically stir for 65 minutes, and obtain the titanium dioxide-silane surface protective agent used in the embodiment. Among them, the silane emulsion used is the isooctyltriethoxysilane emulsion provided by Jacks, and its density is 0.9g / cm 3 , purity is 89%.

[0052] The fly ash used is Class F II fly ash, with a 28d mortar activity of 70%; the microsilica fume is Grade 90, with an activity of 102% and a specific surface area of ​​24,500 m 2 / kg; the density of floating beads is 700kg / m 3 ; The density of expanded perlite is 2600kg / m 3 ;Steel slag sand density is 3650kg / m 3 ; Pebbles are natural pebbles with a grading of 5~26.5mm.

[0053] Example 1

[0054] A crack-resistant green carbon-reducing plain concrete, the formula of which comprises the following components by mass: 500 parts of supersulfate cement, 100 parts of fly ash, 20 parts of microsilica powder, 50 parts of floating beads, 50 parts of expanded perlite, 550 parts of steel slag sand, 980 parts of pebbles, 11.2 parts of viscosity-reducing anti-cracking water-reducing agent, and 160 parts of water; the specific preparation steps are as follows:

[0055] A forced mixer was used to first mix the weighed floating beads, expanded perlite, steel slag sand, pebbles and 40% of the water for 45 seconds, then supersulfate cement, fly ash and microsilica powder were added and mixed for 45 seconds, and finally the remaining water and the viscosity-reducing anti-cracking water-reducing agent were added and mixed for 95 seconds to obtain a mixture. During the mixing, the indoor temperature was 23°C and the relative humidity was 60%. The obtained mixture was poured and molded, and a titanium dioxide-silane surface protective agent was applied on the surface of the obtained molded test block, with a coating amount of 480 g / m 2 Finally, the surface is covered with a film for curing to obtain the anti-cracking green carbon-reducing plain concrete.

[0056] The specific surface area of ​​the super sulfate cement used is 395m 2 / kg, 28d strength is 48.5MPa, wherein the super sulfated cement is composed of 10 parts of carbide slag cement clinker, 85 parts of slag, 5 parts of desulfurized gypsum, and 3 parts of triethanolamine as a grinding aid; the preparation method of the super sulfated cement is: drying the gypsum, adding the grinding aid to the carbide slag cement clinker and ball milling for 20 minutes, adding slag and desulfurized gypsum and mixing and ball milling for 25 minutes.

[0057] The test results show that the 28d compressive strength of the obtained plain concrete can reach 48.6MPa, the slump is 215mm, the expansion is 595mm, the frost resistance grade is F250, the impermeability grade is P24, and the 3d shrinkage rate is 149×10 -6 The total cracking area per unit area can reach 152mm 2 / m 2 .

[0058] Example 2

[0059] A crack-resistant green carbon-reducing plain concrete, the formula of which comprises the following components by mass: 400 parts of supersulfate cement (same as in Example 1), 150 parts of fly ash, 25 parts of microsilica powder, 70 parts of floating beads, 60 parts of expanded perlite, 600 parts of steel slag sand, 930 parts of pebbles, 11 parts of viscosity-reducing anti-cracking water-reducing agent, and 175 parts of water; the specific preparation steps are as follows:

[0060] A forced mixer was used to mix the weighed floating beads, expanded perlite, steel slag sand, pebbles and 35% of water for 40 seconds, and then supersulfate cement, fly ash and modified microsilica powder were added and mixed for 30 seconds. Finally, the remaining water and the viscosity-reducing anti-cracking water-reducing agent were added and mixed for 100 seconds to obtain a mixture. During the mixing, the indoor temperature was 23°C and the relative humidity was 60%. The obtained mixture was poured and molded, and a titanium dioxide-silane surface protective agent was applied on the surface of the obtained molded test block, and the coating amount was 310 g / m 2 Finally, the surface is covered with a film for curing to obtain the anti-cracking green carbon-reducing plain concrete.

[0061] The test results show that the 28d compressive strength of the obtained plain concrete can reach 44.9MPa, the slump is 220mm, the expansion is 610mm, the frost resistance grade is F200, the impermeability grade is P22, and the 3d shrinkage rate is 247×10 -6 The total cracking area per unit area can reach 254mm 2 / m 2 .

[0062] Example 3

[0063] A crack-resistant green carbon-reducing plain concrete, the formula of which comprises the following components by mass: 400 parts of supersulfate cement, 150 parts of fly ash, 25 parts of microsilica powder, 70 parts of bubbling beads, 60 parts of expanded perlite, 600 parts of steel slag sand, 930 parts of pebbles, 11 parts of viscosity-reducing anti-cracking water reducer, and 175 parts of water; using a forced mixer, firstly, the bubbling beads, expanded perlite, steel slag sand, pebbles and 35% of water are stirred together for 40 seconds, then the supersulfate cement, fly ash and modified microsilica powder are added and stirred together for 30 seconds, and finally, the remaining water and the water reducer are added and stirred for 100 seconds to obtain a mixture, and the indoor temperature during stirring is 203°C and the relative humidity is 60%; the obtained mixture is poured and molded, and a titanium dioxide-silane surface protective agent is applied on the surface of the obtained molded test block, and the amount is set to 400g / m 2 Finally, the surface is covered with a film for curing to obtain the anti-cracking green carbon-reducing plain concrete.

[0064] The supersulfate cement used is prepared in the same manner as in Example 1, except that the raw materials are 5 parts of carbide slag cement clinker, 88 parts of slag, 7 parts of desulfurized gypsum, and 4 parts of triethanolamine as a grinding aid.

[0065] The test results show that the 28d compressive strength of the obtained plain concrete can reach 40.9MPa, the slump is 215mm, the expansion is 590mm, the frost resistance grade is F200, the impermeability grade is P20, and the 3d shrinkage rate is 125×10 -6 The total cracking area per unit area can reach 198mm 2 / m2 .

[0066] Comparative Example 1

[0067] A kind of plain concrete, the preparation method of which is substantially the same as that of Example 1, except that: an asphalt protective agent (provided by Zhongke Weiye) is applied on the surface of the obtained molded test block, and the amount is set to 480g / m 2 , and finally the surface is covered with a film for maintenance.

[0068] The test results show that the 28d compressive strength of the obtained plain concrete can reach 48.2MPa, the slump is 215mm, the expansion is 595mm, and the 3d shrinkage is 195×10 -6 The total cracking area per unit area can reach 365mm 2 / m 2 , the surface is brown.

[0069] Comparative Example 2

[0070] A plain concrete, the formula of which comprises the following components in parts by mass: 400 parts of ordinary Portland cement (Qingsong P.O42.5R), 150 parts of fly ash, 25 parts of microsilica powder, 70 parts of bubbling beads, 60 parts of expanded perlite, 600 parts of steel slag sand, 930 parts of pebbles, 11 parts of viscosity-reducing anti-cracking water-reducing agent, and 175 parts of water; using a forced mixer, firstly, the bubbling beads, expanded perlite, steel slag sand, pebbles and 35% of water are stirred together for 40 seconds, then ordinary Portland cement, fly ash and modified microsilica powder are added and stirred together for 30 seconds, and finally, the remaining water and the water-reducing agent are added and stirred for 100 seconds to obtain a mixture, and the indoor temperature during stirring is 23°C and the relative humidity is 60%; the obtained mixture is poured and molded, and a titanium dioxide-silane surface protective agent is applied on the surface of the obtained molded test block, and the amount is set to 310 g / m 2 , and finally the surface is covered with a film for maintenance.

[0071] The test results show that the 28d compressive strength of the obtained plain concrete can reach 45.8MPa, the slump is 185mm, the expansion is 530mm, and the 3d shrinkage is 462×10 -6 The total cracking area per unit area can reach 552mm 2 / m 2 , there are many tiny cracks on the surface that cannot be counted.

[0072] Comparative Example 3

[0073] A kind of plain concrete, the preparation method of which is substantially the same as that of Example 1, except that: the water reducer used is a common polycarboxylic acid water reducer (water reduction rate is 25%) and an anti-cracking admixture (Hebei Tongbang XY-1), and a titanium dioxide-silane surface protective agent is applied on the surface of the obtained molded test block, and the amount is set to 480g / m2 , and finally the surface is covered with a film for maintenance.

[0074] The test results show that the 28d compressive strength of the obtained plain concrete can reach 35.2MPa, the slump is 190mm, the expansion is 555mm, and the 3d shrinkage is 524×10 -6 The total cracking area per unit area can reach 415mm 2 / m 2 .

[0075] Comparative Example 4

[0076] A kind of plain concrete, the preparation method of which is roughly the same as that of Example 1, except that: the raw materials used for supersulfate cement and their weight proportions are: 10 parts of silicate cement clinker, 85 parts of slag powder, 5 parts of anhydrous gypsum, and 3 parts of triethanolamine as a grinding aid; wherein the content of calcium silicate minerals in cement clinker is 64wt%, the content of free calcium oxide is 2.9wt%, and the content of magnesium oxide is 1.5wt%; the content of magnesium oxide in slag powder is 6.8wt%, and the content of vitreous body and dicalcium silicate is 9.2wt%; the preparation method of supersulfate cement is: drying gypsum, mixing cement clinker, slag powder and gypsum, adding grinding aid and ball milling for 45 minutes. The specific surface area of ​​the prepared cement is 355m 2 / kg, and the 28d strength is 41.5MPa.

[0077] The test results show that the 28d compressive strength of the obtained plain concrete is 32.5MPa, the slump is 205mm, the expansion is 555mm, the frost resistance grade is F100, the impermeability grade is P8, and the 3d shrinkage rate is 296×10 -6 The total cracking area per unit area is 392mm 2 / m 2 .

[0078] Comparative Example 5

[0079] A crack-resistant green carbon-reducing plain concrete, the formula of which comprises the following components by mass: 500 parts of supersulfate cement, 100 parts of fly ash, 20 parts of microsilica powder, 50 parts of floating beads, 50 parts of expanded perlite, 550 parts of steel slag sand, 980 parts of pebbles, 11.2 parts of viscosity-reducing anti-cracking water-reducing agent, and 160 parts of water; the specific preparation steps are as follows:

[0080] A forced mixer was used to first mix the weighed floating beads, expanded perlite, steel slag sand, pebbles and 40% of the water for 45 seconds, then supersulfate cement, fly ash and microsilica powder were added and mixed for 45 seconds, and finally the remaining water and the viscosity-reducing anti-cracking water-reducing agent were added and mixed for 95 seconds to obtain a mixture. During the mixing, the indoor temperature was 23°C and the relative humidity was 60%. The obtained mixture was poured and molded, and a titanium dioxide-silane surface protective agent was applied on the surface of the obtained molded test block, with a coating amount of 480 g / m 2 Finally, the surface is covered with a film for curing to obtain the anti-cracking green carbon-reducing plain concrete.

[0081] The preparation method of the water reducer used therein includes: adding 50 parts of β-naphthalenesulfonate formaldehyde condensate, 30 parts of glucose laurate, 3 parts of sodium methoxide, 6 parts of methanol, and 13 parts of polysorbate to 120 parts of water, heating to 60°C, and stirring for 50 minutes to obtain a mixed solution A; then adding 115 parts of water and heating to 60°C, then adding 21 parts of notoginseng saponin, 35 parts of aminobenzenesulfonic acid, 22 parts of methyl silicone oil, 15 parts of lignin, and 15 parts of initiator ammonium persulfate, stirring for 60 minutes to obtain a mixed solution B; then adding the mixed solution A, stirring for 60 minutes, and standing to cool to room temperature 22°C to obtain the water reducer used in the comparative example.

[0082] The test results show that the 28d compressive strength of the obtained plain concrete can reach 33.2MPa, the slump is 185mm, the expansion is 550mm, the frost resistance grade is F100, the impermeability grade is P6, and the 3d shrinkage rate is 452×10 -6 The total cracking area per unit area can reach 524mm 2 / m 2 .

[0083] The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.

Claims

1. A green, crack-resistant, carbon-reducing plain concrete, characterized in that: The components and their weight proportions include: 400-500 parts of super sulfated cement, 100-150 parts of fly ash, 20-30 parts of microsilica powder, 50-100 parts of floating beads, 50-90 parts of expanded perlite, 500-650 parts of steel slag sand, 900-1100 parts of pebbles, 5-15 parts of viscosity-reducing anti-cracking water-reducing agent, and 150-180 parts of water. Meanwhile, a nano titanium dioxide-silane surface protective agent is applied on the surface of the concrete. The super sulfated cement is obtained by ball milling carbide slag cement clinker, slag and desulfurized gypsum as main raw materials. The nano titanium dioxide-silane surface protective agent takes silane emulsion, nano titanium dioxide and epoxy resin as main components and is prepared by a sol-gel method.

2. The green crack-resistant and carbon-reducing plain concrete according to claim 1 is characterized in that: The specific surface area of ​​the super sulfate cement is 380-420 m 2 / kg, and the 28d strength is 45.6~49.5MPa.

3. The green crack-resistant and carbon-reducing plain concrete according to claim 1 is characterized in that: The raw materials in the supersulfate cement and their weight proportions include: 5-10 parts of carbide slag cement clinker, 75-85 parts of slag, and 3-8 parts of desulfurized gypsum.

4. The green crack-resistant and carbon-reducing plain concrete according to claim 1 is characterized in that: The preparation method of the viscosity-reducing anti-cracking water-reducing agent comprises the following steps: 1) Add β-naphthalenesulfonate formaldehyde condensate and polyethylene glycol laurate into water and mix them evenly to obtain a mixed solution A; dilute sodium methoxide, a complex alcohol solvent and polysorbate with water and mix them with the mixed solution A, and heat and stir them; cool them; then add muscovite powder and vermiculite powder, stir them twice, add tripesunobacteria saponin and stir them three times to obtain a mixed solution B; 2) under heating conditions, dodecylbenzene sulfonic acid and polyoxypropylene glycerol ether polyether modified silicone oil are added to water, stirred for four times, an initiator is added and stirred, lignin and carbon fiber are added, stirred for five times, and allowed to stand to reduce the internal temperature to 45-55° C.; then mixed solution B is added, stirred for six times, and allowed to stand to cool to room temperature, thereby obtaining the viscosity-reducing anti-cracking water-reducing agent.

5. The green crack-resistant and carbon-reducing plain concrete according to claim 4 is characterized in that: In the preparation process of the viscosity-reducing anti-cracking water-reducing agent, the raw materials and their weight proportions include: 35-55 parts of β-naphthalenesulfonate formaldehyde condensate, 25-35 parts of polyethylene glycol laurate, 2-5 parts of sodium methoxide, 6-10 parts of composite alcohol solvent, 11-15 parts of polysorbate, 20-35 parts of muscovite powder, 10-25 parts of vermiculite powder, 15-35 parts of tripterygol saponin, 25-55 parts of dodecylbenzene sulfonic acid, 15-25 parts of polyoxypropylene glycerol ether polyether modified silicone oil, 10-20 parts of lignin, 5-10 parts of carbon fiber filaments, and 15-25 parts of initiator.

6. The green crack-resistant and carbon-reducing plain concrete according to claim 1, characterized in that: The preparation method of the nano titanium dioxide-silane surface protective agent comprises the following steps: adding a titanium source to an alcohol solvent in an amount of 5-15%, mixing evenly, and obtaining a liquid A; adding an epoxy resin and nitric acid to the remaining alcohol solvent and mixing evenly, and obtaining a liquid B; adding the liquid B dropwise to the liquid A, stirring once, stopping stirring when the sol becomes milky white, and then adding the obtained titanium dioxide sol to an ultrasonically dispersed silane emulsion, stirring twice, and obtaining the nano titanium dioxide-silane surface protective agent.

7. The green crack-resistant and carbon-reducing plain concrete according to claim 6 is characterized in that: The raw materials in the nano titanium dioxide-silane surface protective agent and their weight proportions include: 5-15 parts of titanium source, 20-45 parts of alcohol solvent, 5-15 parts of nitric acid, 15-30 parts of epoxy resin and 150-180 parts of silane emulsion.

8. The green crack-resistant and carbon-reducing plain concrete according to claim 1 is characterized in that: The amount of the nano titanium dioxide-silane surface protective agent set on the concrete surface is 300-500g / m 2 .

9. The green crack-resistant and carbon-reducing plain concrete according to claim 1, characterized in that: The fly ash is Class F II fly ash, and the 28d mortar activity is 65-70%; the specific surface area of ​​the microsilica powder is 24000-25000cm 2 / g, 28d activity is 100~106%; floating bead density is 650~710kg / m 3 ;Steel slag sand 3620~2680kg / m 3 ; The pebbles are natural pebbles with a grading of 5~26.5mm.

10. The method for preparing the green crack-resistant carbon-reducing plain concrete according to any one of claims 1 to 9, characterized in that: The steps include: 1) Weigh the raw materials according to the proportion. The components and their weight proportions include: 400-500 parts of super sulfate cement, 100-150 parts of fly ash, 20-30 parts of microsilica fume, 50-100 parts of floating beads, 50-90 parts of expanded perlite, 500-650 parts of steel slag sand, 900-1100 parts of pebbles, 5-15 parts of viscosity-reducing anti-cracking water-reducing agent, and 150-180 parts of water; 2) Use a forced mixer to mix the floating beads, expanded perlite, steel slag sand, pebbles and 30-40% of water for a first time, then add super sulfate cement, fly ash and microsilica powder for a second time, and finally add the remaining water and the viscosity-reducing anti-cracking water-reducing agent for a third time to obtain a mixture; 3) pouring and molding the obtained mixture, applying a nano-titanium dioxide-silane surface protective agent on the surface of the obtained molded test block, and finally performing surface coating and curing to obtain the green crack-resistant and carbon-reducing plain concrete.

Citation Information

Patent Citations

  • Calcium carbide slag cement clinker production line process

    CN104086105A

  • High-bending-strength supersulfate cement and preparation method thereof

    CN107827379A